STUDENT SUPPORT AND MOTIVATION IN ONLINE LEARNING: EVIDENCE FROM PILOT ONLINE COURSE IMPLEMENTATION - Rasa Tamulienė; Alina Liepinaitienė; Edvinas Ignatavičius (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose, 2023)
Teaching and learning in a virtual environment bring many changes in the implementation of study content. During online learning, the number of hours of contact learning between the lecturer and students decreases, more attention is paid to students’ self-study. Students lose the opportunity to receive informal emotional support from the academic staff and fellow students, and the sense of community and belonging to a higher education institution decreases. The research presented in the article aims to reveal students’ opinions about students’ support and their motivation during online studies while implementing a pilot online-taught study course. The research was conducted under the Erasmus+ project “Quality of Virtual Studies”. Students from four higher education institutions in Lithuania, Spain, Croatia, and Finland participated in implementing the pilot online learning course. Study courses taught remotely were designed based on the quality assurance criteria for virtual studies developed during the project. Students studied the pilot online-taught study course for three months. They completed questionnaires about their online learning experience twice: before and after they started participating in the course. The study results reveal that the most important source of support for students during online studies is communication with the lecturer. It was established that most students’ support during remote studies is provided by the following means: personal video or email from the lecturer, clear structure of the course studied remotely, clear procedures of the study course, and pre-announced hours of remote consultations with the lecturer. The study reveals that students are most motivated during online studies by receiving feedback from the lecturer, the interest of the academic staff in students’ motivation and motivational tools, a clear study plan of the course studied, the variety of innovative computer technology tools used during online studies, and the contribution of the lecturer, promoting cooperation between learners.